Penerapan Blended Learning Berbasis Zoom Cloud Meeting Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Larutan Elektrolit Dan Nonelektrolit - Junike Rondonuwu; Johny Zeth Lombok (Chemistry Department, Universitas Negeri Manado, 2022)
Blended learning is mixed learning, namely online and face-to-face learning. Because it is still during the Covid-19 pandemic, learning is currently still being carried out online. To support the online learning process, the Zoom Cloud Meeting application is used. The learning process can also be carried out offline but in accordance with the protocol from the government. This study aims to determine student learning outcomes after being given treatment can exceed the KKM value. The study used an experiment with a one shoot case study research design. This research was conducted at SMA Negeri 1 Tutuyan for the academic year 2020/2021 with 29 students in class X MIA 1. The data collection technique was a posttest and the instrument used to measure learning outcomes was a multiple choice test. The results of this study used the t-test one sample t-test with the results of ttable 1.701 and tcount 28.8476 with a significant level of 5% and therefore ttable was smaller than tcount. Thus, it means that H1 is accepted and H0 is rejected. So it was concluded that student learning outcomes after being given treatment can increase and exceed the KKM value.